Central role of pyrophosphate in acellular cementum formation. - Brian L Foster (Public Library of Science (PLoS), 2012)
Background Inorganic pyrophosphate (PP(i)) is a physiologic inhibitor of hydroxyapatite mineral precipitation involved in regulating mineralized tissue development and pathologic calcification. Local levels of PP(i) are controlled by antagonistic functions of factors that decrease PP(i) and promote mineralization (tissue-nonspecific alkaline phosphatase, Alpl/TNAP), and those that increase local PP(i) and restrict mineralization (progressive ankylosis protein, ANK; ectonucleotide pyrophosphatase phosphodiesterase-1, NPP1). The cementum enveloping the tooth root is essential for tooth function by providing attachment to the surrounding bone via the nonmineralized periodontal ligament. At present, the developmental regulation of cementum remains poorly understood, hampering efforts for regeneration. To elucidate the role of PP(i) in cementum formation, we analyzed root development in knock-out ((-/-)) mice featuring PP(i) dysregulation. Results Excess PP(i) in the Alpl(-/-) mouse inhibited cementum formation, causing root detachment consistent with premature tooth loss in the human condition hypophosphatasia, though cementoblast phenotype was unperturbed. Deficient PP(i) in both Ank and Enpp1(-/-) mice significantly increased cementum apposition and overall thickness more than 12-fold vs. controls, while dentin and cellular cementum were unaltered. Though PP(i) regulators are widely expressed, cementoblasts selectively expressed greater ANK and NPP1 along the root surface, and dramatically increased ANK or NPP1 in models of reduced PP(i) output, in compensatory fashion. In vitro mechanistic studies confirmed that under low PP(i) mineralizing conditions, cementoblasts increased Ank (5-fold) and Enpp1 (20-fold), while increasing PP(i) inhibited mineralization and associated increases in Ank and Enpp1 mRNA. Conclusions Results from these studies demonstrate a novel developmental regulation of acellular cementum, wherein cementoblasts tune cementogenesis by modulating local levels of PP(i), directing and regulating mineral apposition. These findings underscore developmental differences in acellular versus cellular cementum, and suggest new approaches for cementum regeneration.